Widen HE access from FE colleges: the key role played by subject tutors. (2nd January 2022) - Raven, Neil
ABSTRACT: The potential for further education colleges (FECs) to contribute to widening higher education access has been recognised in a number of studies. Yet, evidence suggests that higher education participation rates from FECs are lower than from school sixth forms. This article reports on the early findings from a research project that is exploring how colleges could harness their progression potential. The project's starting point is in recognising that many college students do go onto university-level education and training, which suggests that instances of good practice do exist within FECs. In confirming this supposition, the findings highlight the pivotal role that subject tutors can play in supporting progression. Whilst the study calls for the wider recognition and adoption of these practices, the findings also suggest ways in which this support could be enhanced as well as complemented by college-wide activities and outreach initiatives.